Fast Combined Decimal/Binary Multiplier Based on Redundant BCD 4221-8421Digit Recoding - Nabil, Mohammed; Al-Assfor, Fatemah K; Al-Ebadi, Mohammed A. (Basrah Journal for Engineering Sciences, 2017)
Many applications consider floating point arithmetic as a key component of the computations. Combined decimal/binary arithmetic becomes an important topic supports high speed decimal/binary applications. A new 64-bit (16×16 digit) combined decimal/binary multiplier is proposed and implemented in this work that can be used for both fused multiply add (FMA) and multiplier unit. A new partial products reduction tree is shared between decimal and binary multiplier unit. The valuation and comparison result between the proposed multiplier and the previous most recent works shows 4.66 % less delay than combined decimal/binary multiplier and 19.33 % less delay than fastest standalone decimal multiplier.